Efficient Urban Eco-route System for CR-VANETs Based on Air Quality Indexing - Chilukuri, Kalyana Chakravarthy; Musinana, Chandra Sekhar (Research and Developments in Engineering Research Vol. 2, 2023)
The emergence of Cognitive radio (CR) has allowed versatile, efficient and reliable usage of available spectrum. Spectrum may be defined as a fixed band of frequencies to be allocated to nodes for communication via a wireless medium. With advancements in Vehicular technologies, all vehicles are expected to be autonomous intelligent systems that communicate using radio communication interfaces. Vehicular Ad hoc Networks (VANETs), are a category of mobile Ad hoc networks where in the cars are considered to be mobile nodes. This technology has hugely gained in popularity and combined with Cognitive Radio Technology, every vehicle in the near future might be set up with CR interface for intelligent, high-speed communication. This paper addresses the implementation of a popular application of CR-based VANET. In spite of the several ongoing efforts, air pollution continues to pose a serious threat to living beings worldwide. Our proposed method builds a topology with multiple Air Quality Monitors (AQMs) at each traffic signal in urban cities. This enables to provide an eco-route planning system for vehicle users using the measured air quality levels. The attainable routes marked with colored lines based on the air quality levels and attainable values can be conjointly access by users through mobile application.